Leadership server, conceptualization, development and implications for the research (2017)
This review paper describes the main aspects that define and conceptualize the servant leadership. This relatively new concept is being used to refer to an initial arrangement of the leader to focus attention and service to others and how this is being used for leadership development in organizations. Examines proposals around the concept, the evolution of the definition, approach trends, some of critical analysis and prospects and possibilities to constitute an emerging field of research within the administrative, organizational and management sciences. © 2017.